Cake-Hut: A Novel E-Commerce Platform for Booking and Purchasing Cakes Online - H.P.S.M. Tennakoon; R.P.C. Sankalpani; K.A.V. Prabuddhi; D.S. Balage; D.I. De Silva; Dulanji Cooray (International Journal of Engineering and Management Research, 2022)
This research paper proposes an e-commerce cake shopping system: ‘Cake-Hut’ which will enable customers and cake bakery owners to handle their regular online selling and buying activities. Cake Hut is a Web Application where people can purchase customized cakes online from their favorite cake bakery according to their preferred designs or else, they can choose pre-defined cake designs from set of designs which were uploaded by sellers. The system is developed to replace the existing cake purchasing and order management methods, making it more effective and efficient while also addressing user needs. Agile software development methodology approach has been used to develop and test the system in a systematic manner, which includes the development phases of planning, design, and testing and implementation. This system is developed using React JS for frontend development and Express JS for backend development, MongoDB database, and runs on Node JS runtime environment.